Specific features of competition functioning of martial arts elite sportsmen - Radchenko, Y. A. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
Purpose: to study competition functioning of martial arts elite sportsmen. Material: we analyzed 33 competition duels, studied specific features of application of 917 technical tactic actions by sportsmen. We used analysis of video-records of competition duels at All-Ukrainian competitions. Results: it was found that modern martial arts are very dynamic kinds of sports. Victory is won usually by versatile sportsmen, who can quickly to re-construct in the course of duel and successfully use strike and wrestling techniques. Most of duels are won by points. Most of sportsmen compete in standing position, preferring striking technique: straight punches in head and side kicks in torso. It was also found that when using wrestling techniques in standing position, sportsmen prefer different throws by legs’ gripping. When fighting in lying position sportsmen are successful in holding and try to apply painful holds. Conclusions: results of our researches, providing observations of below described conditions, can be a basis for correction of training process; for choosing of means and methods for coaches and instructors of professional training in Armed Forces and law enforcement bodies.